Signals from intestinal microbiota mediate the crosstalk between the lung-gut axis in an influenza infection mouse model - Zhang, Yijia; Wan, Youdi; Xin, Xin; Qiao, Yixuan; Qiao, Wenna; Ping, Jihui; Su, Juan (Frontiers in Immunology, 2024)
Influenza virus primarily targets the respiratory tract, yet both the respiratory and intestinal systems suffer damage during infection. The connection between lung and intestinal damage remains unclear. Our study found that influenza virus infection caused significant damage to both the lungs and intestines, with virus detected exclusively in the lungs. Antibiotic treatment worsened the severity of lung and intestinal damage. Moreover, mRNA levels of Toll-like receptor 7 (TLR7) and Interferon-β (IFN-β) significantly increased in the lungs post-infection. Analysis of intestinal microbiota revealed notable shifts in composition after influenza infection, including increased Enterobacteriaceae and decreased Lactobacillaceae. Conversely, antibiotic treatment reduced microbial diversity, notably affecting Firmicutes, Proteobacteria, and Bacteroidetes. Metabolomics showed altered amino acid metabolism pathways due to influenza infection and antibiotics. Abnormal expression of indoleamine 2,3-dioxygenase 1 (IDO1) in the colon disrupted the balance between helper T17 cell (Th17) and regulatory T cells (Treg cells) in the intestine. Mice infected with influenza virus and supplemented with tryptophan and Lactobacillus showed reduced lung and intestinal damage, decreased Enterobacteriaceae levels in the intestine, and decreased IDO1 activity. Overall, influenza infection caused damage to lung and intestinal tissues, disrupted intestinal microbiota and metabolites, and affected Th17/Treg balance. Antibiotic treatment exacerbated these effects. Supplementation with tryptophan and Lactobacillus improved lung and intestinal health, highlighting a new understanding of the lung-intestine connection in influenza-induced intestinal disease.